2021
DOI: 10.47256/kepariwisataan.v15i01.146
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Museum Sebagai Objek Wisata Edukasi

Abstract: The purpose of this study is to describe or strengthen the function of the museum as a means of education outside the classroom as part of the co-curricular education program. This program is often referred to as an educational tourism activity. This research is a descriptive qualitative research that uses data collection methods through literature study using various sources such as books, journal articles, and news sources that support the research. Data collection, data processing, and data analysis were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
5
0
7
Order By: Relevance
“…Some participants suggested that the museum should expand reservation channels and daily visitor quotas, because "it's challenging to make a reservation" (Participants 4, 12, 15, 24), allowing more people to visit the museum more conveniently and pleasantly. In addition, some participants mentioned issues with the rented audio guide devices (Participant 3) and found that manual explanations lacked interest or storytelling elements (Participants 8, 9, 17, 32), suggesting that they were not as engaging as external tour guides ( Participants 11,12,17,19). The museum's external promotion efforts and the forms and effects of cultural dissemination also serve as important indicators for assessing the museum's service quality.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Some participants suggested that the museum should expand reservation channels and daily visitor quotas, because "it's challenging to make a reservation" (Participants 4, 12, 15, 24), allowing more people to visit the museum more conveniently and pleasantly. In addition, some participants mentioned issues with the rented audio guide devices (Participant 3) and found that manual explanations lacked interest or storytelling elements (Participants 8, 9, 17, 32), suggesting that they were not as engaging as external tour guides ( Participants 11,12,17,19). The museum's external promotion efforts and the forms and effects of cultural dissemination also serve as important indicators for assessing the museum's service quality.…”
Section: Plos Onementioning
confidence: 99%
“…Many interviewees expressed concerns about the presence of noisy children (Interviewees 2, 3,5,11,17,20) and the lack of rest areas (Interviewees 7, 9, 12, 13, 15). In response, museums should consider the learning characteristics and behaviors of children.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Proses komunikasi ke publik dijalankan melalui informasi tentang koleksi museum. Museum memiliki koleksi yang mengandung nilai informasi melalui peran pengelola museum (Prasetyo et al, 2021). Pengelola museum akan menjalankan proses pengadaan koleksi, perawatan, pameran, dan interpretasi.…”
Section: Pendahuluanunclassified
“…Wisata jenis ini juga sebagai study tour atau perjalanan kunjungan-kunjungan pengetahuan (Hadiwijoyo, 2012). Wisata edukasi adalah suatu aktivitas pariwisata yang dilakukan oleh wisatawan yang mengambil liburan sehari dan mereka melakukan perjalanan untuk pendidikan dan pembelajaran sebagai tujuan utama atau tujuan yang kedua (Prasetyo et al, 2021). Wisata edukasi adalah suatu program dimana peserta kegiatan wisata melakukan perjalanan wisata pada suatu tempat tertentu dalam suatu kelompok dengan tujuan utama mendapatkan pengalaman belajar secara langsung terkait dengan lokasi yang dikunjungi (Saeroji, 2022).…”
unclassified